Does head start improve children's life chances? Evidence from a regression discontinuity design - Douglas L. Miller; Jens Ludwig (University of California, Department of Economics, 2005)
This paper exploits a new source of variation in Head Start funding to identify the program s effects on health and schooling. In 1965 the Office of Economic Opportunity (OEO) provided technical assistance to the 300 poorest counties in the U.S. to develop Head Start funding proposals. The result was a large and lasting discontinuity in Head Start funding rates at the OEO cutoff for grant-writing assistance, but no discontinuity in other forms of federal social spending. We find evidence of a large negative discontinuity at the OEO cutoff in mortality rates for children ages 5-9 from causes that could be affected by Head Start, but not for other mortality causes or birth cohorts that should not be affected by the program. We also find suggestive evidence for a positive effect of Head Start on educational attainment in both the 1990 Census, concentrated among those cohorts born late enough to have been exposed to the program, and among respondents in the National Education Longitudinal Study of 1988.
Keywords: I18; I20; I38; 330